Detection of Human Bodies from the Background in an Image Using Piecewise Linear-Support Vector Machine - Dr. Ramana Reddy, Lakshmidhar and (International Journal of Scientific Research and Management (IJSRM), 2017)
- Detection of the human bodies from the background in an image is challenged by the view and posture variationproblem. In this paper, a piecewise linear support vector machine (PL-SVM) method is used for solving the problem ofidentification of humans in an image, which is challenged by the view and posture variation problem. The motivation is, byusing the piecewise discriminative function for constructing a non-linear classification boundary that can differentiatemulti-view and multi-posture human bodies from the backgrounds in a high dimensional feature space. A PL-SVMtraining is designed as an iterative procedure of feature space division and linear SVM training, aiming at the maximizedmarginality of local linear SVM’s. Each piecewise SVM model is responsible for subspace, corresponding to a humancluster of a special view or posture. In the PL-SVM, a cascaded detector is proposed with block orientation features and ahistogram of oriented gradient features. This identification of humans in an image is implemented by using mat lab. Byusing this method, we can also detect the presence of humans in videos also